Case Study Of Ford Motor Company Malaysia Sdn. Bhd. Achieving Strategic Competitiveness In The Malaysian Automobile Industry - Seow, Michael Chor Huat (2007)
The competitiveness of the Malaysian auto industry has also increased tremendously and has caused each player to have a smaller sliceof the market share 'pie' with the entrance of new players. Furthermore, with the liberalization of free trade within the region, competition for vehicles is expected to step up and bring in even more players with their various pricing schemes; possibly one day leading to a price war between auto players.